LANGUAGE POLICY IN THE CONTEMPORARY WORLD: MONOLINGUALISM AND BILINGUALISM PRACTICE AND LANGUAGE ASSIMILATION - Vladimir M. Alpatov (Сравнительная политика, 2015)
Much of what previously characterized the language situation and language policy within states is transferred to the international level due to globalization. We are facing the growing importance of world languages, especially English. However, globalization (at least in the form in which it exists now) does not satisfy the need of identitification for the majority people (except, of course, those for whom English is a mother tongue). This situation can lead to conflicts and even question the effectiveness of globalization processes.